The polimorphism of graves and the distribution of archeological remains in the southwest bronze age Necropolis of Soalheironas (Alcoutim) - Cardoso, João Luís (2014)
The Southwest Bronze Age necropolis Soalheironas (Alcoutim)21 was excavated in 2005 by a team directed by the first author and with ongoing participation of the second. With the results already published in their essential form.The remarkable number of graves,more than thirty, which confirm this necropolis to be one of the most important of Southwest Bronze Age,allowed a careful consideration of their respective architecture and structural characteristics, which led to their typology based on the evidence of their diversity.The distribution of the archeological remains in the excavated graves was also subject of analysis and discussion.A necrópole do Bronze do Sudoeste de Soalheironas (Alcoutim) foi escavada em 2005 , por uma equipa dirigida pelo primeiro dos signatários, com o apoio permanente do segundo e encontra-se já publicada, nos seus traços essenciais.A assinalável quantidade de sepulturas que a integram, mais de uma trintena, que fazem dela, uma das mais importantes do Bronze do Sudoeste, possibilitou uma observação detalhada da respetiva arquitetura e características estruturais, que conduziu à constituição de uma tipologia, tendo presente a diversidade evidenciada. A distribuição dos espólios arqueológicos pelas sepulturas escavadas foi também objeto de análise e discussão